Direct numerical simulation study of water droplets freezing on a horizontal plate - Binh, Pham Duy; Truong, Vu Van; Lien, Nguyen Thi Viet; Cuong, Nguyen Tien; Hoe, Nguyen Dinh; Vinh, Nguyen Tuan; Hung, Vu Van (Vietnam Journal of Science and Technology, 2021)
We present the numerical results of the solidification process of water droplets on a cold plate with different wetting angles. The numerical method used is an axisymmetric front-tracking technique. The water droplets are assumed as a spherical cap and placed on the cold plate which is kept at a subfreezing temperature. At the end of solidification, we obtain a small protrusion shape at the top of the frozen water droplet and its height is also higher than that of the initial water droplet. The frozen water droplets are also compared with the corresponding experimental ones reported in the literature.